2013
DOI: 10.1177/1934578x1300800417
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities, and Phenolic Compounds of Selected Inula species from Turkey

Abstract: Three Inula species, I. viscosa, I. helenium ssp. turcoracemosa and I. montbretiana, collected from different locations of Anatolia were investigated for their antioxidant and antimicrobial potential, and their total phenolic content and phenolic composition. Antioxidant activities of various extracts of the plant parts were measured using DPPH radical scavenging and ABTS assays. Antimicrobial potential of methanol extracts of the plant parts was determined by the agar dilution method against Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
2
40
1
2
Order By: Relevance
“…turcoracemosa , I. montebriana , I.viscosa , I. peacockiana and I. thapsoides ssp. thapsoides varied in wide range from 0.03 to 0.82 % (w/w) . In another study, the average contents of 5‐CQA in 33 samples of I. britannica flowers, stems and aerial parts, 6 samples of I. japonica flowers and 6 samples of I. hupehensis flowers from China were found to be 323, 146, 302, 660 and 296 μg/g DM, respectively .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…turcoracemosa , I. montebriana , I.viscosa , I. peacockiana and I. thapsoides ssp. thapsoides varied in wide range from 0.03 to 0.82 % (w/w) . In another study, the average contents of 5‐CQA in 33 samples of I. britannica flowers, stems and aerial parts, 6 samples of I. japonica flowers and 6 samples of I. hupehensis flowers from China were found to be 323, 146, 302, 660 and 296 μg/g DM, respectively .…”
Section: Resultsmentioning
confidence: 91%
“…thapsoides roots (IC 50 0.14 and 0.11 mg/mL) exhibited the highest DPPH radical scavenging activity, while the water extracts of I. helenium flowers, I. thapsoides ssp. thapsoides roots and I. peacockiana leaves (IC 50 0.05, 0.01 and 0.04 mg/mL, respectively) were the best ABTS .+ scavengers . Recently, it has been found that TPC in the AcOEt extract of I. viscosa leaves from Algeria (299.1 mg GAE/g DE) was significantly higher than those reported for the methanol extracts from the flowers of same species, originating from Hebron and Tunisia (173.1 and 103 mg GAE/g DW, respectively) .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, the TPH amount showed significant differences due to solvent of extraction and to varieties. In this context, Gökbulutet al [33] found that the TPH contents of three Inula from Turkey were varied from 21.1 to 190.9 mg GAE/g extract.…”
Section: Aroma Distributionmentioning
confidence: 99%